The Association Between Infant Massage Frequency, Body Mass Index, and Early Psychomotor Milestones Among Infants Aged 3–12 Months: An Analytical Observational Study in Aligned with SDG 3 - Haryani, Siti; Adimayanti, Eka; Astuti, Ana Puji; Minardo, Joyo; Nurcahyo, Satria Avianda (Journal of Applied Nursing and Health, 2026)
Background: Infant massage is a non-invasive, low-cost intervention that supports early childhood growth and development and is increasingly promoted in community health programs. However, evidence on its relationship with Body Mass Index (BMI) and early psychomotor milestone achievement in low- and middle-income countries, particularly Indonesia, remains limited. Therefore, this study aimed to examine the effect of infant massage on BMI and early psychomotor milestones among infants aged 3–12 months in alignment with Sustainable Development Goal 3 (Good Health and Well-Being). Methods: This study used a quantitative design with multiple linear regression analysis. The population consisted of infants aged 3–12 months in Semarang Regency, Indonesia, with a purposive sample of 250 infants. Inclusion criteria were good health status, age 3–12 months, and parental consent, while infants with congenital anomalies or developmental disorders were excluded. BMI was the dependent variable, and independent variables included infant massage frequency, psychomotor milestone achievement, feeding adequacy, and parental stimulation. Data were collected using WHO-standardized BMI measurements and psychomotor milestone checklists. Infant massage followed the standardized Love Baby Massage technique. Ethical approval was obtained, and data were analyzed using multiple linear regression with p-values, confidence intervals, and effect sizes reported. Results: Descriptive analysis indicated that the majority of infants received regular massage and exhibited nutritional status within the WHO reference standards. Regression analysis demonstrated that infant massage frequency and psychomotor milestone achievement were significant predictors of BMI (p < 0.05). Feeding adequacy showed a positive association with BMI and a moderate effect size, while parental stimulation exhibited a smaller and statistically nonsignificant direct effect. Collectively, the independent variables contributed substantially to explaining variations in BMI among infants aged 3–12 months. Conclusion: Regular infant massage plays a meaningful role in improving BMI and supporting early psychomotor development. Integrating massage practices with adequate nutrition and parental engagement is recommended as a comprehensive strategy to optimize infant growth and early development, consistent with SDG 3.